2015
DOI: 10.1111/ejn.12940
|View full text |Cite
|
Sign up to set email alerts
|

Graded hypoxia acts through a network of distributed peripheral oxygen chemoreceptors to produce changes in respiratory behaviour and plasticity

Abstract: Respiratory behaviour relies critically upon sensory feedback from peripheral oxygen chemoreceptors. During environmental or systemic hypoxia, chemoreceptor input modulates respiratory central pattern generator activity to produce reflex-based increases in respiration and also shapes respiratory plasticity over longer timescales. The best-studied oxygen chemoreceptors are undoubtedly the mammalian carotid bodies; however, questions remain regarding this complex organ's role in shaping respiration in response t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…1a . Some of the neuron types are identifiable based on their size, color, location, and electrophysiological characterisctics 10 , 45 – 47 . In the left lateral region of the visceral ganglion, a cluster of ~15–18 cells with diameters of ~45–105 µm can be identified as the Fgp neurons 48 .…”
Section: Resultsmentioning
confidence: 99%
“…1a . Some of the neuron types are identifiable based on their size, color, location, and electrophysiological characterisctics 10 , 45 – 47 . In the left lateral region of the visceral ganglion, a cluster of ~15–18 cells with diameters of ~45–105 µm can be identified as the Fgp neurons 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous intracellular current clamp recordings and Lucifer yellow (LY) dye injections were performed as previously described for in vitro 41 and in situ 86 preparations. Briefly, for cultured neurons, cells were maintained in CM or DM (in mM: 40 NaCl; 1.7 KCl; 4.1 CaCl 2 ; 1.5 MgCl 2 ; 5 HEPES; pH 7.9), and glass microelectrodes (resistance 20–50 MΩ) were filled with a saturated solution of K 2 SO 4 .…”
Section: Methodsmentioning
confidence: 99%
“…More recent research efforts of our lab have also focused on dissecting the roles of other environmental signals in the modulation of respiratory CPG activity and the plasticity of aerial breathing behavior. Using a combination of behavioral and electrophysiological approaches, we have recently reported that Lymnaea possesses a spatially distributed network of peripheral oxygen chemoreceptor sites that respond selectively to graded hypoxic challenges. , These findings suggest that the existence of multiple oxygen chemoreceptor sites is an evolutionarily conserved strategy that underlies the adaptability of respiratory behavior to meet changing environmental demands, and opens to new opportunities to investigate the fundamental synaptic mechanisms that regulate respiratory systems.…”
Section: Identification and Reconstruction Of Simple Neuronal Circuit...mentioning
confidence: 98%
“…The animals can be made to rely entirely on aerial respiration by exposure to hypoxic conditions such as nitrogenated water, which makes the analysis of this behavior easy to achieve under strictly regulated and reproducible experimental conditions. Aerial respiration in Lymnaea is controlled by a reciprocal inhibitory synapse between the visceral dorsal 4 (VD4) and input 3 interneurons (IP3I), which activate distinct visceral K (VK) and visceral J (VJ) motoneurons that drive inspiration and expiration, respectively , (Figure B,C). This arrangement of a mutually inhibitory synapse driving antagonistic motor functions via alternating bursts of activity paralleled the “half-center” oscillator model that had been proposed to underlie the expression of many rhythmic behaviors under study in both vertebrate and invertebrate models, where rhythmic network activity could result from reciprocal antagonistic synaptic connections between two neurons or two populations of neurons. , However, direct and unequivocal experimental evidence supporting the necessity and sufficiency of a half-center oscillator network in the expression of rhythmic behaviors proved difficult to obtain.…”
Section: Identification and Reconstruction Of Simple Neuronal Circuit...mentioning
confidence: 99%